Analisis Pemanfaatan Minyak Nabati Sebagai Alternatif Bahan Bakar Kompor - Hamri - - (Teknik Mesin "TEKNOLOGI", 2010)
The aim of study for benefit 100% of vegetable oil (castor oil and coconut oil as fuel of pressure stove, without bio fuel process than petroleum, comparison of flaming who happen and emission from 3 of fuel, and what if fuel vegetable oil more economize than petroleum. Procedure of riset is examinee the experiment every fuel to blaze using pressure stove. then measure emission from result of burning from three fuel. to measure temperature of flaming from 3 fuel who burning and examine how long time for to finish fuel with fixed volume from fuel. Result to show time of normal burning for petroleum 1 till 2 minutes, castor oil 12 minutes and coconut oil 15 minutes. emission from burning result of 3 fuel find CO2 is highest at petroleum that is 1,06 %, castor oil 0,66 % and cocounut oil is 0,54 %. time for to finish fuel with fixed volume 200 cc is longest is castor oil that is 36 minutes 27 second,vegetable oil 35 minutes 5 second and petroleum 26 minutes 35 second, temperature of flaming stove from 3 fuel average of result measuring to find 300°C with touch time of flaming fire is 1 minutes.